2021
DOI: 10.1038/s41598-021-86526-2
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning and ensemble stacking technique for differentiating polypoidal choroidal vasculopathy from neovascular age-related macular degeneration

Abstract: Polypoidal choroidal vasculopathy (PCV) and neovascular age-related macular degeneration (nAMD) share some similarity in clinical imaging manifestations. However, their disease entity and treatment strategy as well as visual outcomes are very different. To distinguish these two vision-threatening diseases is somewhat challenging but necessary. In this study, we propose a new artificial intelligence model using an ensemble stacking technique, which combines a color fundus photograph-based deep learning (DL) mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The OCT-based model alone reached an accuracy of 83.2%, and the bimodal DL model combining fundus and OCT images had an improvement in accuracy of 87.4%. Another study from Chou et al 67 showed a comparable result. They proposed a bimodal model with an ensemble stacking technique, combining color fundus photographs (CFPs) and clinical features of OCT biomarkers to distinguish between PCV and nvAMD with an accuracy of 83.67%, sensitivity of 80.76%, and specificity of 84.72%.…”
Section: Discussionmentioning
confidence: 69%
“…The OCT-based model alone reached an accuracy of 83.2%, and the bimodal DL model combining fundus and OCT images had an improvement in accuracy of 87.4%. Another study from Chou et al 67 showed a comparable result. They proposed a bimodal model with an ensemble stacking technique, combining color fundus photographs (CFPs) and clinical features of OCT biomarkers to distinguish between PCV and nvAMD with an accuracy of 83.67%, sensitivity of 80.76%, and specificity of 84.72%.…”
Section: Discussionmentioning
confidence: 69%
“…Going one step further, there have been attempts to classify AMD using fundus photographs and OCT. Using the two modalities, Chou et al differentiated PCV from nAMD with EfficientNet and multiple correspondence analysis 22 . Moreover, Xu et al classified nAMD, Dry AMD, PCV, and normal groups using deep CNN networks 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Wet AMD develops in these people when aberrant blood vessels develop into the retina and leak fluid, making the retina “wet.”. If CNV is left untreated it will lead to vision loss [ 34 ]. There are many works in the literature to find out the CNV using deep learning, machine learning techniques but the main concern of this work is to focus on the diabetic retinopathy-based lesions therefore, not going much deeper into this section it will review some of the work in the literature so that one may have the overview about this lesion type.…”
Section: Dr Screening Methodsmentioning
confidence: 99%
“…Yu-Bai Chou et al 2021 [ 34 ], uses a deep learning and ensemble stacking for CNV categorization. This research could provide an alternate way for constructing a multimodal DL framework, enhance its ability to differentiate between disorders, and clinical sciences more widely applicable in DL model construction.…”
Section: Dr Screening Methodsmentioning
confidence: 99%